Phenolic and flavonoid amounts and antioxidant capacity of Lavandula officinalis (lavender) callus grown in different growth regulator combinations - Kaygusuz, Oğuzhan; Sengul, Meryem Senay (My University, 2022)
In this study, it was aimed to determine the total antioxidant capacity and phenolic and flavonoid amounts of Lavandula officinalis (lavender), which is an aromatic plant, callus extracts. Combinations of Naphthalene Acetic Acid (NAA), Benzylaminopurine (BAP), Kinetin (KIN) and 2,4-Dichlorophenoxy Acetic Acid (2,4-D) plant growth regulators at different concentrations were used in the growth medium. The specified analyzes were carried out for the extracts obtained from the callus of plants grown in different media. The callus were extracted with water and ethanol solvents. Total phenolic amount analyzes were accomplished using the Folin-Ciocalteu method. The spectrophotometric AlCl3 method was used for the total flavonoid amount analysis and the antioxidant capacity of lavender callus extracts was measured considering the radical cation capture ability of 2,2?-azino-bis -3- ethylbenzthiazoline -6- sulphonicacid (ABTS). The highest antioxidant capacity (9.24 ± 0.14 mmol TEAC/g dry callus weight) was obtained from the callus of plants grown in medium containing 0.5 mg/L BAP + 0.5 mg/L 2,4-D combination; the highest amount of phenolic substance (35.74± 0.48 mg GAE/g dry callus weight) was obtained from the callus of plants grown in medium containing the combination of 0.5 mg/L BAP + 0.5 mg/L NAA; the highest amount of flavonoid substance (32.42 ± 0.46 mg QE/g dry callus weight) was obtained from the callus of plants grown in medium containing the combination of 0.5 mg/L BAP + 1 mg/L 2,4-D. The results are compared for the combination of plant growth regulators and the effects of the different growth medium ingredients were specified.
Keywords: Flavonoid; fenolik; Antioksidan; kallus; Antioxidant; flavonoid; Callus; Plant Growth Regulator; Lavandula officinalis; Phenolic; bitki büyüme düzenleyici